A partial skeleton of the tritheledontid Pachygenelus (Therapsida: Cynodontia) - Gow, Chris E (Bernard Price Institute for Palaeontological Research, 2001)
Tritheledontids are advanced cynodonts that are considered the sister group of Mammalia. To date the postcranial skeleton has remained largely unknown, so that cladistic analyses are based on cranial characters only. This paper describes a specimen of the tritheledontid Pachygenelus which has most of the skull and vertebral column, a complete shoulder girdle, and most of the forelimb. The girdle and limb are closely comparable to those of Massetognathusand Eozostrodon, and unlike these elements in tritylodontids, which are more derived for fossorial specialisations.
Keywords: Therapsida; Pachygenelus; postcranial skeleton